Features of innovative management of reformatory changes in system of the land relations - ZRYBNIEVA, IRYNA; Zavolichna, Tetyana (The USV Annals of Economics and Public Administration, 2017)
In the article the authors investigated the state of land reform in Ukraine evaluated the prospects of its development following on from the experience of Bulgaria, Romania and Hungary. An innovative algorithm of change management in the system of administration of land relations was suggested, which role is to provide opportunities to expeditiously manage land conversion, effectively overcome resistance to change.
Keywords: land relations; land reform; reflexive management; price of land; antroposocial contexts; organizational contexts; functional contexts